Papua New Guinea food price bulletin: April 2023 - International Food Policy Research Institute; Hayoge, Greg; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2023)
Download time series food price data, and build graphs and tables for over 20 different food crops at our food price database webpage: https://www.ifpri.org/project/freshfood-price-analysis-papua-newguinea. In the first quarter of 2023, the average price of sweet potatoes (except in Port Moresby) and taro declined by 14 and 17 percent, respectively, in all markets. Rice prices remained stable in all markets during the 1st quarter of 2023, however long-term (2021 real) rice price (1 kilo bag) has increased 13% between the 2nd quarter of 2021 and the 1st quarter of 2023. Leafy vegetables (aibika, choko-tips, English cabbage, pakchoi) prices increased 31 percent (in nominal terms) in Kokopo between January and March. However, average green leafy vegetable prices in Port Moresby decreased by 19 percent, except for Aibika. In Mt Hagen, choko-tips and pakchoi prices were up by 27 percent from January, while aibika and English cabbage decreased by 11 percent between January and March.